Libraries at the Crossroads of the Digital Content Divide: Pathways for Information Continuity in a Youth-Led Geospatial Technology Program. Issue 3 (1st September 2016) - Masucci, Michele; Organ, David; Wiig, Alan
Abstract : This article reviews the implementation and outcomes of a social action research, university-community partnership titled Building Information Technology Skills (BITS). BITS trains high school–age youth in geographic field methods to gather and analyze geospatial information as a means of fostering their civic engagement and motivation to persist in the study of Science, Technology, Engineering and Math (STEM) disciplines. The program was designed from its inception to be culturally, historically, and geographically relevant. In order to accomplish this, the authors leveraged access to and use of the Charles L. Blockson Afro-American Collection as a beginning point for the youth in the program to consider and focus on the relationships between place, history, and digital geospatial technologies. This was achieved by introducing the youth involved in the program to geographic information through an inventory of historic markers depicting African American sites of interest in Philadelphia. The primary aim of the social action methods employed was to simultaneously increase the interest, engagement and geographic skills among the youth participants and to create a digital archive related to the historic markers that could in and of itself become a resource for the education of youth and community members in Philadelphia. Use of the Blockson Collection anchored the program's goals of a) advancing digital inclusion and digital content creation among relatively under-represented communities and b) promoting youth empowerment by fostering the development of STEM skills and engagement within a university setting. In grounding the acquisition of field methods and geospatial information technology skills in an understanding of local history and culture, the BITS program mutually reinforces the dual-objective of advancing STEM engagement and creating a more-empowering geography for students to learn from.